Acute Toxicity Tests of Basil Leaves (Ocimumsanctum) Ethanolic Extract Determined By LD50 and Renal Histopathology - Cholis Abrori; Khana Nurfadhila; Elly Nurus Sakinah (Journal of Agromedicine and Medical Sciences, 2019)
Basil leaves are widely used as herbal remedies and have proven many benefits because the content of phytonutrients includes antioxidants, but at certain doses a compound retains a probability of causing toxicity in the body. This study aims to determine the acute toxicity of ethanolic extract of basil leaves seen from the value of LD50 range and renal histopathology which is the vital organ of the target of toxicity in the body. The method of acute oral toxicity test was OECD 420 fix dose procedure method with a group of 5 Balb/c female mice given a multilevel dosage. The initial dose is 2000 mg/Kg.b.w selected on a sighting study as a dose that may cause mild toxicity symptoms but does not cause death. There are 2 groups consist of treatment with dose at LD50 value and control. The result of this research showed that LD50 value of ethanol extract of Ocimum sanctum > 2000 mg/Kg.b.w. The mean renal histopathologyc scores between the control and the treatment were significantly different by The Mann-Whitney test with significance value of p=0.018. Ocimum sanctum ethanolic extract is classified as non-toxic compounds but there was a change in renal histopathology of mice in the form of focal lesions after acute exposure at highest dose of OECD 420 method. Keywords: acute toxicity test, renal histopathology, basil leaves